Stakeholder analysis towards unpacking communities of practice for transdisciplinary research and action in climate change and health in Africa - Atela, Joanes; Bolo, Emily; Agevi, Humphrey; Muindi, Kanyiva; Thiam, Sokhna; Gordon, Ezekiel; Wanjiru Irungu, Ann; Gitau, Hellen (Frontiers in Human Dynamics, 2024)
Health and climate drivers and solutions in Africa co-exist within the same social context. Primary healthcare systems are increasingly becoming impacted by climate change. Health and climate change communities still work in isolation in addition to limited multidisciplinary and integrated research on health and climate change to inform programming, and policy and unlock climate finance. Holistic and transdisciplinary approaches that make use of resources and inputs from different sectors are key to guaranteeing effective responses to the health impacts of climate change. This paper aims to understand the landscape of climate and health (C&H) research, policy capacity building, and stakeholders hence identifying models of collaboration that could be scaled up to strengthen transdisciplinary C&H research and action. A mixed method approach was used in this study that involved the combination of consultative webinars (n = 411) online surveys (n = 198), Focused Group Discussions (n = 123), and Key informant interviews (n = 25) used on targeted stakeholders. In addition, a scoping review of policy academic documents, and databases was done. It was evident that engaging partners from diverse sectors is crucial for the broad range of perspectives, interests, skills, levels of knowledge, and resources. Stakeholder engagement in C&H initiatives is increasing and yet unevenly distributed in Africa due to funding patterns and other structural patterns. Existing C&H research predominantly focuses on climate impacts on diseases, particularly vector-borne and infectious illnesses. While crucial, this disease-centric approach limits the provision of integrated solutions for complex African socio-economic contexts. In addition, Dedicated C&H capacity-building efforts are emerging, but they mainly focus on research and policy, overlooking critical areas like leadership, investment skills, and impact assessment. Health governance and climate change should be addressed through a holistic approach that is transdisciplinary and multisectoral and through the transborder framework. The approach will need innovative thinking in socio-economies, policies, ecologies, and geographies with emphasis centered on the most vulnerable groups.